Rasgos de personalidad disocial y la terapia cognitivo conductual en adolescente fugitivo - Reyes Ortega, Ruben Dario (2019)
The present research work covers a problem very common but treated as object of study and analyzed to find a reason for dissocial behaviors in adolescents, which mostly have a great impact on adult life, involving them in organizations criminals, in this particular case, influenced the behavioral state of a 12-year-old student, with consequences that characterize this type of situation, this issue involves considerable attention by psychologists. We describe a clinical case diagnosed with dissociative disorder, a study that was carried out on a student of the Clemente Baquerizo Educational Unit, which had effects on the emotional, behavioral and student areas. It was recognized which the most influential factors in the maintenance of symptoms during the application of various psychological techniques in interviews and later in interventions, with the application of a scheme of cognitive behavioral therapy